Activation-induced cytidine deaminase is a possible regulator of cross-talk between oocytes and granulosa cells through GDF-9 and SCF feedback system - Takashi Iizuka (Nature Portfolio, 2021)
Abstract Activation-induced cytidine deaminase (AID, Aicda) is a master gene regulating class switching of immunoglobulin genes. In this study, we investigated the significance of AID expression in the ovary. Immunohistological study and RT-PCR showed that AID was expressed in murine granulosa cells and oocytes. However, using the Aicda-Cre/Rosa-tdRFP reporter mouse, its transcriptional history in oocytes was not detected, suggesting that AID mRNA in oocytes has an exogenous origin. Microarray and qPCR validation revealed that mRNA expressions of growth differentiation factor-9 (GDF-9) in oocytes and stem cell factor (SCF) in granulosa cells were significantly decreased in AID-knockout mice compared with wild-type mice. A 6-h incubation of primary granuloma cells markedly reduced AID expression, whereas it was maintained by recombinant GDF-9. In contrast, SCF expression was induced by more than threefold, whereas GDF-9 completely inhibited its increase. In the presence of GDF-9, knockdown of AID by siRNA further decreased SCF expression. However, in AID-suppressed granulosa cells and ovarian tissues of AID-knockout mice, there were no differences in the methylation of SCF and GDF-9. These findings suggest that AID is a novel candidate that regulates cross-talk between oocytes and granulosa cells through a GDF-9 and SCF feedback system, probably in a methylation-independent manner.